2023
DOI: 10.3390/vaccines11030583
|View full text |Cite
|
Sign up to set email alerts
|

Zika Vaccine Microparticles (MPs)-Loaded Dissolving Microneedles (MNs) Elicit a Significant Immune Response in a Pre-Clinical Murine Model

Abstract: Although the global Zika epidemic in 2015–16 fueled vaccine development efforts, there is no approved Zika vaccine or treatment available to date. Current vaccine platforms in clinical trials are administered via either subcutaneous or intramuscular injections, which are painful and decrease compliance. Therefore, in the present study, we explored Zika vaccine microparticles (MPs)-loaded dissolving microneedles (MNs) with adjuvant MPs encapsulating Alhydrogel® and MPL-A® administered via the transdermal route … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The study of MN delivery of vaccine antigen against SARS-CoV-2 has been in preclinical testing. However, this study reports the effects of the integration of microparticulate vaccine delivered via MN [ 14 , 40 , 47 ]. A phase 1 clinical trial was conducted for the “PittCoVacc” vaccine, which administered the spike protein suspension in an MN-based vaccine [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of MN delivery of vaccine antigen against SARS-CoV-2 has been in preclinical testing. However, this study reports the effects of the integration of microparticulate vaccine delivered via MN [ 14 , 40 , 47 ]. A phase 1 clinical trial was conducted for the “PittCoVacc” vaccine, which administered the spike protein suspension in an MN-based vaccine [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microneedles were formulated using the spin-casting method previously established in our laboratory [ 14 , 15 , 47 , 62 , 64 ]. First, depending on the group, the corresponding RBD suspension, RBD MPs, and adjuvant MPs were added to the trehalose solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we investigated our ZIKV MP vaccine with Alhydrogel ® (alum) and Monophosphoryl Lipid-A (MPL-A ® ) adjuvants in microparticulate form. Alhydrogel ® (alum) helps to stimulate a T-cell helper Th2 antibody-mediated response [ 21 ]. On the other hand, MPL-A ® helps to induce a Th1 T-cell helper response.…”
Section: Introductionmentioning
confidence: 99%
“…There are several types of microneedles, such as solid microneedles and hollow microneedles; however, dissolving microneedles is one of the most sought-after methods of intradermal vaccination due to the fact of their versatility in loading different kinds of antigens [21]. Moreover, dissolving microneedles can also be loaded with different nanoparticles that will simply be released in the skin upon application [18,[22][23][24]. We have previously shown that when the F-VLP antigen is encapsulated into a PLGA polymeric nanoparticle matrix, it improves the immunogenicity in vitro [25].…”
Section: Introductionmentioning
confidence: 99%